Mindfulness-Based Group Approach for Undergraduate Students with Disordered Eating or Body Image Issues: A Case Study - Stumpf, Olivia (Building Healthy Academic Communities Journal, 2017)
Background: Mindfulness can be defined as "consciously bringing awareness to the present moment by focusing non-judgmentally on cognitions, emotions, and physical sensations" (Kabat-Zinn, 1994). This technique is applicable to patients with disordered eating, body image issues, or eating disorders (EDs) because these individuals have a tendency to become detached from their emotions and use the over or under consumption of food to regulate their internal state (Corstorphine, 2006). Mindfulness techniques are used to create a connection between thoughts, feelings and physical sensations, and external experiences. Practicing mindful eating is one way undergraduate students can be attentive to hunger cues and ensure balanced nutrition amidst a full academic schedule. Aim: The aim of the study was to develop and evaluate a mindfulness-based group approach to managing eating disorders in college students with disordered eating or body image issues. Methods: Undergraduate students ages 18 to 22 years old who were already receiving treatment for ED symptomatology from a university Counseling & Psychological Services Center were recruited to participate in a six-week mindfulness-based group approach to eating awareness. Results from the progress of two participants’ process observations are shared. Results: Increases were seen in participants’ confidence in using mindfulness-based practices to foster a sense of acceptance, nurturance, and adaptive behaviors. Conclusions: A mindfulness-based group approach to treatment of disordered eating or body image issues shows promise for improving the quality of life for college-aged students. Undergraduate institutions have the advantage of using social interaction to facilitate healthy behavioral change. Future research with larger and more diverse samples is suggested, and implications regarding practice and education are also discussed.